Programa educativo de evaluación 360° para desarrollar capacidades de la autoconsciencia en estudiantes de quinto grado de secundaria en el colegio Mariscal Oscar R. Benavides Iquitos 2024 - Huamán Coral, Rosa Mercedes (2025)
The research aimed to assess the impact of the 360° evaluation educational program on the development of self-awareness capabilities among fifth-grade secondary students at Colegio Mariscal Óscar R. Benavides, Iquitos, 2024. A field, longitudinal and univariate evaluative design was required, which included a sample of 64 students, divided into two groups: one experimental and the other control. The data collection technique involved a standardized test, complemented by a written performance assessment, an instrument validated by experts. The findings showed that, at the beginning of the investigation, both groups showed similar levels in the Pretest, with a high percentage at the "beginning" level (96.9% and 93.8%). However, when comparing the Posttest results, the experimental group showed a significant improvement, evidenced by a reduction in the "beginning" level (93.8% to 0%) and a significant increase in the "in progress" (6.3% to 65.6%), "expected achievement" (0% to 28.1%), and "outstanding achievement" (0% to 6.3%) levels. These findings indicate that the 360° evaluation educational program had a positive effect on the development of self-awareness capabilities, promoting advances in the emotional, cognitive, and social dimensions of the students, which contributed to achieving the set objectives.